Association between Helicobacter pylori infection and tumor markers: an observational retrospective study. Issue 8 (23rd August 2018) - Xu, Mei-Yan; Cao, Bing; Chen, Yan; Musial, Natalie; Wang, Shuai; Yin, Jian; Liu, Lan; Lu, Qing-Bin
Abstract : Objective: Helicobacter pylori infection is a major cause of several cancers such as gastric, pancreatic and lung. The relationship between H. pylori and tumour markers continues to remain unclear. The primary goal of this study is to clarify the associations between H. pylori infection and six tumour markers (ie, carcinoembryonic antigen (CEA), cancer antigen (CA) 153, CA199, CA724, CA125 and alpha-fetoprotein (AFP)). The secondary goal is to provide understanding for further research about H. pylori infection and gastrointestinal cancer. Design: Observational retrospective study. Setting: The study was performed in Beijing, China, where enrolled subjects had all passed health examinations during the period of 2012–2016. Subjects were categorised into H. pylori (+) and H. pylori (–) group according to their infection status and the measured six biomarkers. We used logistic regression models and generalised linear models to explore the associations between H. pylori infection and six tumour markers (ie, CEA, CA153, CA199, CA724, CA125 and AFP). Participants: A total of 14 689 subjects were included and 6493 (44.2%) subjects were infected by H. pylori . The subjects had a mean age (1SD) of 45 (18) years. There were 4530 (31.0%) female subjects. Results: After adjusting for the confounding factors, infections with H. pylori were found to be significantly associated with abnormal ratios in CEA, AFP and CA724 of H. pylori (+) to H. pylori (–) groups. Significant positive correlation was found between H. pylori infection and CEA values (adjusted β= 0.056; 95% CI 0.005 to 0.107; p=0.033). Conclusions: In this observational retrospective study, we observed the H. pylori infections in a Chinese population and found higher CEA level in H. pylori -infected subjects and abnormal ratios in CEA, AFP and CA724 in infected subjects to uninfected subjects. These findings may provide a basis for future exploration with H. pylori and tumour markers.